Giant dermoid cyst of ovary in postmenopausal woman: a case report - Ghose, Seetesh; G., Chandana; Rathod, Setu; John, Lopamudra B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
A 49 year, miltipara, post-menopausal woman complains of pain abdomen and breathlessness for one week. On abdominal examination, there was a firm mass. MRI showed multi-loculated cystic lesion suggestive of ovarian dermoid cyst. Patient underwent TAH and BSO.